Advances in ITP - therapy and quality of life - a patient survey - Matzdorff, Axel; Arnold, Gabriele; Salama, Abdulgabar; Ostermann, Helmut; Weigold, Sonja; Hummler, Simone (PLOS ONE, 2011)
Background Current guidelines recommend glucocorticoids and splenectomy as standard 1st and 2nd line treatments for chronic immune thrombocytopenia (ITP). We sought to find out how German ITP-patients are treated with respect to these guidelines. Methods Members of a patient support association ≥18 years with a self-reported history of chronic ITP>12 months were surveyed with a web-based questionnaire. Results 122 questionnaires were evaluated. 70% of patients had chronic ITP for more than 5 years and 20% an average platelet count of ≤30·109/L. 41% of the patients reported haematomas or petechiae more than once or twice and up to 12 times or more per year and 17% oropharyngeal and nasal bleeds. 11% had been admitted to hospital during the last 12 months. 88% had received or currently receive glucocorticoids, 27% were splenectomised. IVIG had been given to 55%, rituximab to 22%, anti-D to 12%, ciclosporin to 7%, while complementary and alternative medical treatments had been used by 36%. 50 women responded to questions concerning pregnancy. 14 (28%) had been advised not to become pregnant. 23 reported pregnancies and 10 (44%) required treatment for their ITP during pregnancy. Conclusion Glucocorticoids are the most common therapy for chronic ITP but complementary and alternative treatments already come second and less than ⅓ of patients are splenectomised. This and the frequent use of complementary medicines suggests patients' dissatisfaction with conventional approaches. Many patients receive off-label therapies. There is a major need for adequate counselling and care for pregnant ITP-patients.
Gesehen am 12.08.2022